Ευρεία επιχείρηση έρευνας - διάσωσης αλλοδαπών στην ευρύτερη θαλάσσια περιοχή νοτιοανατολικά ν. Χίου (HellenicCoastguard, 2021)
: Βασίλειο, Βασίλειο, Βασίλειο, Βασίλειο, Βασίλειο. Βασίλειο, Βασίλειο, Βασίλειο. Βασίλειο, Βασίλειο.